LITERASI NUMERIK DI SD SWASTA PKMI EFESUS AEK BATU - Frida Marta Argareta Simorangkir; Dyan Wulan Sari HS (Universitas Negeri Medan, 2021)
Abstract: Numeric Literacy in Elementary School PKMI Efesus Aek Batu. The purpose of this study is to describe (1) the implementation of numerical literacy in learning, (2) efforts to overcome obstacles in numerical literacy, (3) supporting factors and (4) inhibiting factors of numerical literacy. This type of research is descriptive qualitative. The results of the research are (1) the implementation of numerical literacy in learning based on three stages, namely the stages of habituation, development, and learning and according to the five indicators of numerical literacy. (2) The efforts made to overcome the obstacles in numerical literacy are in accordance with the literacy goals in schools. (3) The supporting factors are all school members who are the targets of implementing numerical literacy. And (4) the inhibiting factors are reviewed based on the class base, school culture and society.Keyword : Literacy, Numeric, Elementary SchoolAbstrak :Literasi Numerik di SD Swasta PKMI Efesus Aek Batu. Tujuan penelitian ini untuk mendeskripsikan (1) pelaksanaan literasi numerik dalam pembelajaran, (2) upaya mengatasi kendala dalam literasi numerik, (3) faktor pendukung dan (4) faktor penghambat literasi numerik.Jenis penelitian adalah deskriptif kualitatif. Hasil penelitian yaitu (1) pelaksanaan literasi numerik dalam pembelajaran berdasarkan tiga tahapan yaitu tahap pembiasaan, pengembangan, dan pembelajaran serta sesuai dengan lima indikator literasi numerik. (2) Upaya yang dilakukan untuk mengatasi kendala dalam literasi numerik sudah sesuai pada tujuan literasi di sekolah. (3) Faktor pendukung yaitu seluruh warga sekolah yang menjadi sasaran pelaksanaan literasi numerik. Dan (4) Faktor penghambat ditinjau berdasarkan basis kelas, budaya sekolah dan masyarakat.Kata kunci : literasi, numerik, sekolah dasar